Técnicas de modulação para redução da tensão de modo comum em sistemas fotovoltaicos conectados à rede - Ferreira, José Ramon Nunes (2021)
The research proposes to investigate the modulation technique with the One-Cycle Control (OCC) applied to three-phase inverters, with a focus on reducing the Common Mode Voltage (CMV) in photovoltaic systems connected to the grid. The proposed method is explained by its mathematical modeling, being compiled in a photovoltaic system plant (processed in the dedicated Matlab software for simulations), with a power generation capacity of 3kW, composed of a matrix of photovoltaic plates and an inverter. of three-phase voltage. The simulation results of the OCC technique are compared with results of the SVPWM technique already published in the literature. The Common Mode Voltage is considered a problem in electrical systems. Its emergence occurs by Electromagnetic Interference - EMI usually caused by non-linear loads connected to the electrical network. Electronic devices that operate with low nominal voltage values are more susceptible to CMV. In systems connected to the grid, CMV causes complications in supplying the voltage generated by the PV array, transmitting harmonic currents to the grid. The OCC controller has a relevant characteristic in the perspective of reducing the Common Mode Voltage in photovoltaic systems connected to the grid, thus pointing out improvements in the quality of the output voltage signal produced by these systems.